1992
DOI: 10.1007/bf00172594
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebral chemotherapy in the 9L rat brain tumor model

Abstract: We have used the 9L rat brain tumor model to search for effective chemotherapeutic approaches to the management of brain tumors. Several antineoplastic agents which have been proposed or are currently being used for human brain tumors, including 1,3-bis (2-chloroethyl)-1-nitrosourea (BCNU), bleomycin, aziridinylbenzoquinone (AZQ), cis-Platinum, and acivicin, were administered intravenously (iv), intraperitoneally (ip), or intracerebrally (ic) to rats burdened with the intracranial 9L gliosarcoma. The results c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…It has been extensively used to study chemotherapy and radiation effects (Henderson et al, 1981; Wen et al, 1990; Kimler et al, 1992; Kruse et al, 1993). Recently, it has also been used to study tumour stem cells (Ghods et al, 2007).…”
Section: L Glioma Modelmentioning
confidence: 99%
“…It has been extensively used to study chemotherapy and radiation effects (Henderson et al, 1981; Wen et al, 1990; Kimler et al, 1992; Kruse et al, 1993). Recently, it has also been used to study tumour stem cells (Ghods et al, 2007).…”
Section: L Glioma Modelmentioning
confidence: 99%
“…These studies frequently use rodent brain tumor models (7)(8)(9)(10), particularly the rat 9L tumor (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Animal survival, colony-forming efficiency (CFE) assays of cells disaggregated from solid tumors, and measurements of excised tumor weights have been used for two decades to quantitate the efficacy of various treatments on the orthotopic 9L brain tumor (11)(12)(13)(14)(15)(16)(17)(18)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Numerous in vitro and in vivo studies have shown that 1,3-bis(2-chloroethyl)-1-nitrosourea (BCNU) is an effective treatment for the 9L brain tumor (11-15, 17, 18, 20-23, 25-29); in fact, a single bolus of BCNU achieved a 3-4 log cell kill in orthotopic tumors, resulting in a 97% increase in life span (13).…”
mentioning
confidence: 99%
“…It has been used extensively to evaluate the responses of brain tumors to a variety of therapeutic modalities, including chemotherapy (75)(76)(77)(78)(79), radiotherapy (75,80), combinations of chemo-and radiotherapy (22,77), immunotherapy (81)(82)(83)(84), the combination of chemo-and immunotherapy (85), effects of blood-brain barrier disruption on uptake of chemotherapeutic agents (69,70,86), boron neutron-capture therapy (BNCT) (87,88), and, most recently, for gene therapy (89)(90)(91)(92)(93)(94)(95)(96)(97)(98)(99)(100)(101)(102)(103)(104). Impressive therapeutic results have been obtained in a number of these studies, including eradication of the tumor.…”
Section: L Gliosarcomamentioning
confidence: 99%